Estimulador elétrico neuromuscular bifásico com saída em ponte H isolada eletricamente - Gaiotto, Marcelo do Carmo Camargo (2012)
The electronics used in the development of functional electrical stimulators include huge diversification of techniques and technologies, whose solutions for the output stage range from transistor circuits (bipolar or MOSFET), to pulse transformers and high-voltage operational amplifiers. To develop a biphasic neuromuscular electrical stimulator with electrically isolated H-bridge output. The electrical neuromuscular stimulation system contains biphasic H-bridge output using only N-channel MOSFET transistors, allowing the generation of mono and biphasic pulses whose pulse amplitudes are independently controlled by a flexible electronics platform, which enables its use with different types of control elements, from microcontroller and FPGA devices to Labview virtual instrument. Bench tests were performed that allowed to assess the performance of the instrument and all its modules separately. The power range used in the tests was 12 to 24V, the technique is directly related to generate the high voltage used which allowed to produce 280 V to 300 V, used in the H bridge, which in turn performed as expected providing pulses biphasic with peak to peak values of 600 V, which pudendal have its amplitude pulses individually controlled with a resolution of 73.26 mV (step 4096), thus allowing the generation of stimulatory different patterns created from the graphical interface. The project developed led the design of a new technique for H-bridge output using transistors N-channel MOSFET in the construction of biphasic neuromuscular electrical stimulator with independent amplitude control for each pulse. Such functionality can contribute to new studies and rehabilitation using neuromuscular electrical stimulation, whereas through the graphical user interface created stimulatory specific waveforms can be generated.